Study of the Transplantation Process of Cultured Epidermis Containing Pigmented Cells - Takeuchi, Takayuki; Tomochika, Mayo; Nabeshima, Ryota; Kajikawa, Akiyoshi; Sumie, Rena; Kubota, Manabu; Inoue, Hajime (The St. Marianna Medical Journal, 2021)
Purpose: Cultured epithelium grafting is an effective and relatively less invasive medical technique for the treatment of extensive vitiligo. However, the results obtained after grafting are not stable because the conventional culture technique only maintains the melanocytes present in the epithelial cell culture but does not support melanocyte growth. To solve this problem, we established an epithelial cell culture technique that can regulate the melanocyte content. In this study, we investigated the viability and persistence of melanocytes in cultured epithelium cells. Methods: Cultured epidermis was prepared at epidermal cell/pigment cell ratios of 1: 0.01, 1: 0.1, and 1:1. These cultured epithelial sheets were then grafted subcutaneously into immunodeficient mice, and the tissues were collected after periods of 2 weeks and 3 months, for histological examination. Results: Survival of the pigmented epithelium was confirmed after 2 weeks. The grafted cultured epithelium contained Melan-A positive cells and melanin granules (as detected with Giemsa staining). The number of melanocytes in the cultured epithelium after grafting changed according to the ratio of seeded melanocytes. The viability of the cultured epithelium and melanocytes was also confirmed in the tissue collected 3 months after transplantation. Moreover, Giemsa staining demonstrated the presence of melanin granules in these pigmented cells. The melanocytes in the grafted epithelium tested positive for Dopa reaction, 3 months after the transplantation. Conclusion: The cultured epithelium containing melanocytes was able to proliferate in vivo, and the melanocytes survived and maintained their functions, even in the long term. Therefore, this technique may provide a better color-matched treatment for vitiligo vulgaris in the future.